Motivasi Sebagai Pendorong Produktivitas Kerja - Wahyuni , Ririn; Azizah , Nur; Agustuti Handani , Lusi; Afifi , Abdullah; Mu’alimin (Idarotuna : Journal of Administrative Science, 2024)
As a driver of job productivity in this topic, performance motivation is thought to be the primary factor in accomplishing results. Data was gathered through a literature study, which involved gathering sources of information from multiple library resources, using a qualitative methodology. Subsequently, the study's findings demonstrate that a number of tactics are thought to be successful in boosting employee productivity at work. These tactics include recognizing accomplishments, fostering positive interpersonal relationships, connecting communication with a supportive atmosphere, and allocating suitable responsibilities. The research's findings emphasize the significance of management's role in creating a work environment that enhances performance motivation and the necessity of appreciating the elements that influence employee motivation and the implementation of HR strategies in businesses. This study offers a valuable theoretical and practical contribution to our understanding of successful strategies for boosting employee morale in order to meet corporate objectives.